Avaliação do herbicida saflufenacil no controle de Ipomoea grandifolia (Dammer) O’Donell e Euphorbia heterophylla L. no sistema de cana crua - Costa, Saulo Italo de Almeida [UNESP] (2014)
The effectiveness of herbicides in raw cane agricultural system is directly impacted by the amount and distribution of straw in the field, which intercept the herbicide before it reaches the ground as well as the occurrence of rain after application. Thus, this study aimed to evaluate the effectiveness of the herbicide saflufenacil alone and mixed with adjuvant to control of Euphorbia heterophylla and Ipomoea grandifolia weeds in sugarcane mechanical harvesting without straw burning, as well as its selectivity to the culture. The study was carried out in three phases: one in greenhouse and two at the field (Lençóis Paulista - SP and Teotônio Vilela - AL) with different doses of saflufenacil herbicide, with or without rain simulation, at different times after application of chemical treatments. The treatments were: saflufenacil (0.050 kg ha- 1); saflufenacil (0.070 kg ha-1); saflufenacil (0.140 kg ha- 1); saflufenacil + Dash (0.050 kg ha-1 + 0.5 % v / v); saflufenacil + Dash ( 0.070 kg ha-1 + 0.5% v / v); saflufenacil + Dash ( 0.140 kg ha-1 + 0.5% v / v) and mesotriona + Assist ( 0.3 L.ha-1 + 0.5% v / v ), which were applied on 12 t ha-1 of straw on the ground, as well as spraying on the soil without straw coverage, in the presence or absence of simulated rain (amount of 11 mm) after spraying of the chemical treatments. To the 3, 7, 14, 21 and 28 days after application (DAA), the percentage of control was evaluated and at 28 DAA the dry biomass of the weed species was evaluated. The saflufenacil herbicide applied in post-emergence was effective to control of I. grandifolia and E. heterophylla weeds. The weed I. grandifolia proved to be more sensitive to treatment with the saflufenacil herbicide. The presence of straw and the absence of rain facilitated the control of I. grandifolia, while the presence of straw and rain did not facilitated the control of E. heterophylla. The adjuvant addition to ...